Indikator Risk Based Bank Rating, Kinerja Keuangan dan Perusahaan Perbankan - Bayu Indrawan, Ida Bagus Made; Wirasedana, I Wayan Pradnyanta (E-Jurnal Akuntansi; Vol 31 No 3 (2021)DO - 10.24843/EJA.2021.v31.i03.p20, 2021)
The research aims to prove empirically the influence of Non-Performing Loans, Loans to Deposit Ratio, Good Corporate Governance, Net Interest Margin, and Capital Adequacy Ratio on financial performance of banking companies listed on the IDX. Agency theory and Productive theory of credit are the theories used in this study. The study population is all Banking Companies listed on the Indonesia Stock Exchange (IDX) in 2014-2018 totaling 45 companies. The research sample of 30 companies with non-probability sampling method with purposive sampling technique. The data analysis technique used is multiple linear regression. The research results obtained by Non Performing Loans are considered negative, Loan to Deposit Ratio and Good Corporate Governance are not approved and are significant, Net Interest Margin and Capital Adequacy Ratio have positive and significant effect on financial performance. Keywords: Non Performing Loan; Loan to Deposit Ratio; Good Corporate Governance; Net Interest Margin; Capital Adequacy Ratio; Financial Performance.